DINAMIKA PERBEDAAN PENDAPAT DALAM FORMULASI KOMPILASI HUKUM ISLAM PADA ASPEK HUKUM WARIS, HIBAH DAN WASIAT - Is, Muhammad Fadhlan (Jurnal AL-AHKAM, 2019)
History records that the success in the effort to formulate a compilation of Islamic law was overshadowed by differences of opinion from several Islamic legal thoughts at that time. Moreover, there are many offers to include customary law and BW that are familiar to Muslims in the country into the KHI material. The emergence of differences of opinion among ulama is due to many factors, including their differences in using arguments, the method of ijtihad and understanding the al-Qur'an and Sunnah texts, the background, social, educational, and cultural backgrounds of the KHI formators at that time. This study uses a descriptive qualitative research approach. This study answers the hypothesis that certain social values and solidarity play an important role in the conclusions of a legal product. In collecting data in this study, the authors used two techniques, namely direct interviews and documentation. Direct interviews with figures involved in formulating KHI and several Islamic legal experts who are seen as understanding the issues being studied. Also reviewing data from other sources such as documentation related to KHI formulations such as journals, newspapers, magazines, study manuscripts at the beginning of the KHI preparation and other sources of information. The results of the study show the fact that the formulation of KHI through a structural approach is top down from the central government, but still involves the role of the ulama, scholars and practitioners of Islamic law. KHI material absorbs fiqh that is familiar in the country. The dynamics of differences of opinion are found in three patterns of Islamic Law thought that emerged at that time. First, the literalisasi group, which is a group that opposes thoughts that violate the nash qat'i. Secondly, the group is assimilative, this group tries to find a new interpretation in understanding nash qat'i. The three groups are Harmonized, Characteristics of this group may be out of zahir nash, if  judging there are provisions that can be an alternative, inheritance is included in the category of mu'amalat worship which must be open to accepting changes by considering the interests and eliminating the narrowness in society.History records that the success in the effort to formulate a compilation of Islamic law was overshadowed by differences of opinion from several Islamic legal thoughts at that time. Moreover, there are many offers to include customary law and BW that are familiar to Muslims in the country into the KHI material. The emergence of differences of opinion among ulama is due to many factors, including their differences in using arguments, the method of ijtihad and understanding the al-Qur'an and Sunnah texts, the background, social, educational, and cultural backgrounds of the KHI formators at that time.This study uses a descriptive qualitative research approach. This study answers the hypothesis that certain social values and solidarity play an important role in the conclusions of a legal product. In collecting data in this study, the authors used two techniques, namely direct interviews and documentation. Direct interviews with figures involved in formulating KHI and several Islamic legal experts who are seen as understanding the issues being studied. Also reviewing data from other sources such as documentation related to KHI formulations such as journals, newspapers, magazines, study manuscripts at the beginning of the KHI preparation and other sources of information.The results of the study show the fact that the formulation of KHI through a structural approach is top down from the central government, but still involves the role of the ulama, scholars and practitioners of Islamic law. KHI material absorbs fiqh that is familiar in the country. The dynamics of differences of opinion are found in three patterns of Islamic Law thought that emerged at that time. First, the literalisasi group, which is a group that opposes thoughts that violate the nash qat'i. Secondly, the group is assimilative, this group tries to find a new interpretation in understanding nash qat'i. The three groups are Harmonized, Characteristics of this group may be out of zahir nash, if  judging there are provisions that can be an alternative, inheritance is included in the category of mu'amalat worship which must be open to accepting changes by considering the interests and eliminating the narrowness in society.